The effectiveness and cost-effectiveness of the NHS Diabetes Prevention Programme (NHS-DPP): the DIPLOMA long-term multimethod assessment - Peter Bower; Claudia Soiland-Reyes; Carole Bennett; Lisa Brunton; Patrick Burch; Elaine Cameron; Tarani Chandola; Georgia Chatzi; Sarah Cotterill; David P French; Judith Gellatly; Mark Hann; et al. (Health and Social Care Delivery Research)
Background Type 2 diabetes is considered a critical challenge to modern healthcare systems. The National Health Service Diabetes Prevention Programme delivered an evidence-based behaviour change programme at a national scale to reduce the incidence of type 2 diabetes in England. Objective(s) The Diabetes Prevention – Long-term Multimethod Assessment research programme provided a comprehensive assessment of the delivery of the National Health Service Diabetes Prevention Programme and its effectiveness and cost-effectiveness. Design Mixed-methods research including qualitative methods, observations, patient surveys and secondary analysis of administrative and survey data using statistical and econometric methods. Setting Community settings in England delivering the commissioned intervention, supported by general practices responsible for recruitment and referral. Participants Patients in community settings identified as being at high risk of type 2 diabetes offered and participating in the National Health Service Diabetes Prevention Programme, and staff involved in the organisation and delivery of the service. Interventions The National Health Service Diabetes Prevention Programme, including its evidence-based behaviour change intervention (using both face-to-face and digital platforms) and the associated services for patient recruitment. Main outcome measures Incidence of type 2 diabetes, cost-effectiveness, access to the programme and fidelity of intervention delivery. Data sources Interviews with patients and staff, document analysis and observations of the National Health Service Diabetes Prevention Programme delivery, patient surveys, secondary data (including National Health Service Diabetes Prevention Programme data, national surveys and audits). Results The National Health Service Diabetes Prevention Programme was associated with significant reductions in incidence of type 2 diabetes and was highly likely to be cost-effective. Analyses of the delivery of the programme highlighted several aspects which impacted access to the programme and the fidelity with which the behaviour change intervention was delivered. For example, uptake and adherence were influenced by participants’ psychosocial beliefs (e.g. chance of getting type 2 diabetes and whether taking part would reduce this). There were large differences between general practices in how many people they referred to the programme, with practices that offered higher-quality care for people with diabetes referring more. Variation in retention and outcomes was associated with differences in providers. Limitations Analysis of administrative data to explore effectiveness and cost-effectiveness may be influenced by confounding. Recruitment of diverse and representative samples for surveys, interviews and observations was likely impacted by selection. Conclusions The National Health Service Diabetes Prevention Programme is highly likely to be cost-effective. Data from Diabetes Prevention – Long-term Multimethod Assessment have been used to improve aspects of programme delivery and could suggest further enhancements to improve recruitment, retention and fidelity. Future work Future research should address the question of whether the National Health Service Diabetes Prevention Programme prevents or delays type 2 diabetes when longer-term follow-up data are available. We identified factors that could be targeted to impact on recruitment, retention and inequalities, and recommend a robust assessment of the link between fidelity and outcomes. Funding This synopsis presents independent research funded by the National Institute for Health and Care Research (NIHR) Health and Social Care Delivery Research programme as award number 16/48/07. Plain language summary The National Health Service Diabetes Prevention Programme was launched in 2016 to reduce the number of people getting type 2 diabetes. This 9-month course offers support to improve diet and exercise to people at high risk of type 2 diabetes. An online course was also offered from 2019. The Diabetes Prevention – Long-term Multimethod Assessment research programme tested whether the National Health Service Diabetes Prevention Programme works better than usual National Health Service care for reducing risk, and whether the National Health Service Diabetes Prevention Programme provides value for money. The research also studied who joins, what makes people take part, how the course is delivered, and what benefits are achieved. We: did interviews with participants, staff, course providers, and National Health Service Diabetes Prevention Programme leaders ran surveys and observed courses across England analysed data from national surveys, general practitioner records and the programme providers shared results with National Health Service England to help them make improvements. We found: Decisions to join were influenced by individuals’ personal views of their chance of getting type 2 diabetes and whether taking part would reduce this. There were large differences between general practices in how many people they referred to the programme, with practices that offered higher-quality care for people with diabetes referring more. Levels of participation in the course and the benefits participants achieved varied. There were differences between populations in rates of joining and completing the programme. For instance, younger adults and people in areas of higher deprivation were less likely to join. People from ethnic minorities were more likely to join but were less likely to complete the course. The programme reduced cases of type 2 diabetes, at a cost that offered value for money. Overall, we found the National Health Service Diabetes Prevention Programme is achieving positive results, but there are opportunities to make it better in future.